Prevalence patterns, virulence indices, and antibiotics resistance in Campylobacter - Manal Hadi Ghaffoori Kanaan, Fatten Ahmad Mohammed, Sura Saad Abdullah (Journal of Applied Pharmaceutical Science, 2024)
Infections caused by Campylobacter are consistently ranked among the top four leading causes of severe diarrheal enteritis throughout the globe. It is a common type of food poisoning, with symptoms ranging from mild to severe. Campylobacteriosis affects over 550 million people each year and kills approximately 33 million. More than 90% of cases are attributed to Campylobacter jejuni (C. jejuni), while only around 5% are attributed to Campylobacter coli (C. coli). Human campylobacteriosis is most usually caused by improper handling of raw chicken carcasses or eating of inadequately prepared poultry. Campylobacteriosis cases frequently resolve on their own with only supportive care. In extreme cases, macrolides and fluoroquinolones are employed. Gentamicin is an aminoglycoside and is the treatment of choice for severe instances of bacteremia as well as other forms of systemic infections with Campylobacter. Selection pressure resulting from misuse and abuse of antibiotics in both human and veterinary medicine is a main contributing factor in the evolution and spread of resistance in commensal bacteria as well as in human illnesses. Therefore, this paper aims to highlight the occurrence, pathogenicity, treatment options, and antibiotic resistance of this pathogen.
Keywords: Antimicrobial resistance, Campylobacter infections, treatment, virulence factors